2010
DOI: 10.1108/17538371011056057
|View full text |Cite
|
Sign up to set email alerts
|

Good and simple – a dilemma in analytical processes?

Abstract: Purpose -The purpose of this paper is to describe the transfer of experiences to improve the basis for overcoming the dilemma of trying to achieve analyses and systems that are both good and simple. The quality of decisions relating to projects depends on how well the assumed basis for the project actually fit the reality of the situation in which the consequences occur. Good value and cost estimations support good decisions about projects insofar as the assumptions on which they are based mirror the reality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 12 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…There seems to be challenges with defining the purpose of the analysis, identifying uncertainty elements, quantification of effects, calculation and estimation and communication of the results from the analysis. It is concluded that [2]:…”
Section: Methods and Processes For Risk-and Uncertainty Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…There seems to be challenges with defining the purpose of the analysis, identifying uncertainty elements, quantification of effects, calculation and estimation and communication of the results from the analysis. It is concluded that [2]:…”
Section: Methods and Processes For Risk-and Uncertainty Managementmentioning
confidence: 99%
“…The dilemma between good and simple in analytical processes have been discussed [2]. There seems to be challenges with defining the purpose of the analysis, identifying uncertainty elements, quantification of effects, calculation and estimation and communication of the results from the analysis.…”
Section: Methods and Processes For Risk-and Uncertainty Managementmentioning
confidence: 99%
See 3 more Smart Citations